Effect of iso-thermal treatment on the corrosion behaviour of low carbon steel (Nigerian C2R grade) in a buffered solution containing chloride and carbonate ions (2012)
This work has investigated the corrosion behavior of low carbon steel subjected to four different modes of iso-thermal heat treatment and then immersed in a neutral buffer corrosive medium containing carbonate and chloride ions. The low carbon steel material was cut into twenty small pieces of length 18±2mm, put in groups of five and subjected to: Annealing, Hardening, Normalizing and tempering, each corresponding to an iso-thermal mode of treatment. The samples were ground and polished, and micrographs taken for each mode of treatment. The samples were then immersed into the corrosion medium; a neutral buffer and samples were withdrawn for measurement every 72 hours. The experiment lasted 360 hours (15 days). The weight loss due to corrosion of the samples, the corrosion rate of the samples and the pH variation of the samples were monitored against time of exposure. It was observed that samples which had undergone tempering mode of heat treatment turned out to be the ones with the best corrosion resistance.